2018
DOI: 10.1002/ece3.3823
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to fluctuations in temperature by nine species of bacteria

Abstract: Rapid environmental fluctuations are ubiquitous in the wild, yet majority of experimental studies mostly consider effects of slow fluctuations on organism. To test the evolutionary consequences of fast fluctuations, we conducted nine independent experimental evolution experiments with bacteria. Experimental conditions were same for all species, and we allowed them to evolve either in fluctuating temperature alternating rapidly between 20°C and 40°C or at constant 30°C temperature. After experimental evolution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 41 publications
2
40
0
Order By: Relevance
“…In a recent study of multiple species of bacteria, Saarinen et al. () found that the clones evolved in the fluctuating environment were more tolerant to environmental fluctuations than the clones evolved in the constant environment. Studies of antibiotic resistance also suggest that less frequent, but stronger antibiotic treatments are more likely to cause the local extinction of the bacterial population (Wu et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study of multiple species of bacteria, Saarinen et al. () found that the clones evolved in the fluctuating environment were more tolerant to environmental fluctuations than the clones evolved in the constant environment. Studies of antibiotic resistance also suggest that less frequent, but stronger antibiotic treatments are more likely to cause the local extinction of the bacterial population (Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ketola et al (2013) observed that strains of bacterial pathogen Serratia marcescens that evolved in fluctuating temperature outperformed in novel environment the strains that evolved in constant temperature. In a recent study of multiple species of bacteria, Saarinen et al (2018) found that the clones evolved in the fluctuating environment were more tolerant to environmental fluctuations than the clones evolved in the constant environment. Studies of antibiotic resistance also suggest that less frequent, but stronger antibiotic treatments are more likely to cause the local extinction of the bacterial population (Wu et al 2014) In a frequently changing environment, similarity of threats affects the level of adaptation When the environment changes frequently relative to the time scale defined by the mutation rate (comparably to the expected time needed to get mutation at a particular locus), there is no time for populations to adapt to the current threat.…”
Section: Rare Environmental Changes Lead To Higher Fitness Lossmentioning
confidence: 99%
“…Insights about the suitability of a thermal landscape for a given species should consider not only average thermal values but also variability in thermal values (Bozinovic, Medina, Alruiz, Cavieres, & Sabat, ; Bozinovic, Sabat, Rezende, & Canals, ; Estay, Lima, & Bozinovic, ). Theoretical (Katz, Brush, & Parlange, ) and empirical studies (Easterling et al., ) have demonstrated that daily and seasonal variation in temperature affects organisms’ ecology and fitness (Clavijo‐Baquet et al., ; Gilbert & Miles, ; Kielland, Bech, & Einum, ; Messenger & Flitters, ; Roitberg & Mangel, ; Saarinen, Laakso, Lindström, & Ketola, ). In addition, thermal extremes, defined as events that alter the distribution of ambient temperature without influencing the mean and the variance (Ummenhofer & Meehl, ), have also been shown to have outstanding effects on physiological performance and survival (Bozinovic, Medina, et al., ; Kingsolver & Woods, ).…”
Section: Introductionmentioning
confidence: 99%
“…A straightforward explanation for these observations is adaptation of Caedibacter to high-temperature stress, just like it is observed in experiments with free-living bacteria 345 (Bennett et al 1992;Saarinen et al 2018), where adaptation of growth rate occurs over similar time spans. Increased heat resistance may therefore allow Caedibacter to attain viable 15 within-host densities, track the regular dilution, when host cells divide, and thereby achieve a high fidelity and rate of vertical transmission.…”
Section: Evolution Of Increased Infection Persistence and Vertical Trmentioning
confidence: 56%